Risk factors predicting Candida infective endocarditis in patients with candidemia. (15th October 2019) - Foong, Kap Sum; Sung, Abby; Burnham, Jason P; Kronen, Ryan; Lian, Qinghua; Salazar Zetina, Ana; Hsueh, Kevin; Lin, Charlotte; Powderly, William G; Spec, Andrej
Abstract: Candida infective endocarditis (CIE) is a rare but serious complication of candidemia. Incidence and risk factors associated with CIE among candidemic patients are poorly defined from small cohorts. Identification of clinical predictors associated with this entity may guide more judicious use of cardiac imaging. We conducted a retrospective analysis of all inpatients aged ≥18 years diagnosed with candidemia at our institution. CIE was diagnosed by fulfilling two of the major Duke criteria: specifically a vegetation(s) on echocardiogram and positive blood cultures for Candida spp. We used univariable and multivariable regression analyses to identify risk factors associated with CIE. Of 1, 873 patients with candidemia, 47 (2.5%) were identified to have CIE. In our multivariable logistic model, existing valvular heart disease was associated with a higher risk for CIE (adjusted odds ratio [aOR], 7.66; 95% confidence interval [CI], 2.95–19.84). Predictors that demonstrated a decreased risk of CIE included infection with C. glabrata (aOR, 0.17; 95% CI, 0.04–0.69), hematologic malignancy (aOR, 0.09; 95% CI, 0.01–0.68), and receipt of total parenteral nutrition (aOR, 0.38; 95% CI, 0.16–0.91). The 90-day crude mortality for CIE was 48.9%, similar to the overall non-CIE mortality of 41.9% ( P  = .338). We identified a set of clinical factors that can predict the presence of CIE among patient with candidemia. These findings may reduce the need for unnecessary expensive and invasive imaging studies in a subset of patients with a lower risk profile for endocarditis and alternative infection source.